Mudharabah serta Musyarakah dalam Praktik Lembaga Keuangan Syariah - Arsela, Mika; Zen, Muhamad (STAINI Press, 2025)
Islamic financial institutions record extraordinary circumstances achieved at ever-changing intervals that can be recognized by cosmopolitan technology. This reflection talks about the differences and similarities between mudharobah and musyarakah in the participation of Islamic financial institutions. The euphemistic disposition possessed in reflection is a qualitative disposition with a creative writing approach. Each collection is hand-collected and explained thereby nailing down a well-controlled process. This reflection states that the persistence of understanding mudharobah and musyarakah in the beginnings of Islamic finance has differences and similarities, these differences can be seen from the understanding, basic sharia, actions in Islamic financial institutions, capital, patronage management, ratios and risks. These patches of similarity complete the distortion of facts in business goals and complications.